2014
DOI: 10.2478/10004-1254-65-2014-2480
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Pathogenic Fungi in Seeds of Different Pea Cultivars in Poland

Abstract: Legume crops are exposed to infection by fungal pathogens, which often results in contamination with mycotoxins. The aim of this study was to evaluate the level of field resistance/susceptibility of edible and fodder pea cultivars to the colonization of seeds by fungal pathogens in two subsequent seasons, as well as to identify the pathogens present in the seeds of the tested cultivars. Alternaria spp. were the most common fungi isolated from pea seeds in both seasons, followed by Fusarium spp., Stemphylium sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The strains were collected, purified and characterized genetically and phenotypically during previous studies (Stępień et al, 2011b;Waśkiewicz et al, 2013). Strains from asparagus and pea were isolated from asymptomatic spears and seeds, respectively (Wilman et al, 2014), the remaining strains came from diseased host plants (data not shown). They are stored in the KF pathogenic fungi collection at the Institute of Plant Genetics, Polish Academy of Sciences, Poznań, Poland.…”
Section: Fungal Strains Media and Biomass Measurementmentioning
confidence: 99%
“…The strains were collected, purified and characterized genetically and phenotypically during previous studies (Stępień et al, 2011b;Waśkiewicz et al, 2013). Strains from asparagus and pea were isolated from asymptomatic spears and seeds, respectively (Wilman et al, 2014), the remaining strains came from diseased host plants (data not shown). They are stored in the KF pathogenic fungi collection at the Institute of Plant Genetics, Polish Academy of Sciences, Poznań, Poland.…”
Section: Fungal Strains Media and Biomass Measurementmentioning
confidence: 99%
“…The predominant species ofsaprotrophic fungi were Alternaria alternata and Cladosporium cladosporioides (Table 3). Alternaria alternata was also most frequently isolated from pea seeds in Poland by Marcinkowska (2008) and Wilman et al (2014). In studies by Horoszkiewicz-Janka et al 2013and Okorski and Majchrzak (2008), pea seeds were colonized by both saprotrophic and pathogenic fungi.…”
Section: Resultsmentioning
confidence: 97%
“…Molecular techniques also supported the identification of three Fusarium species viz. F. verticilloides, F. proliferatum and F. poae in pea seeds grown in Poland (Wilman et al 2014).…”
Section: Resultsmentioning
confidence: 97%
“…2 and Table 1 ). As a consequence, the contamination of plant tissues with fumonisins appears as very likely, since F. proliferatum often synthesizes FBs in infected plant tissues [ 1 , 8 , 35 , 36 ]. Among 44 Fusarium isolates purified during the present study, while F. proliferatum and F. sporotrichioides were the prevailing species, only six F. oxysporum isolates were found (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%